Farmers’ perceptions and level of adoption of technological innovation in shallot cultivation - Wahyuni Budiarti Sri; Cahyaningrum Hermawati; Haryuni Haryuni; Widowati Rahayu; Anshori Arif (E3S Web of Conferences)
Shallot is one of the staple commodities in Indonesia. Increasing consumption needs and high demand for shallots represent a potential market opportunity for farmers to increase shallot production. The research aimed to determine farmers’ perceptions, the influence of farmers’ internal and external characteristics on perceptions of applying shallot cultivation technology, and trends in technology adoption. The research was conducted in Karang Kalasan Village, Kalasan District, Sleman Regency, D.I. Yogyakarta from March to May 2021. Data was collected through a survey using a questionnaire from 25 participants. Data were analyzed descriptively, percentages, frequency tables, Likert scales, and Spearman Rank correlation. The research showed that farmers had a positive perception of technological innovation in shallot cultivation. Farmers considered that shallot cultivation technology is profitable, suits people’s needs, is not complicated, is triable and the results are observable. The characteristics of gender, length of experience in shallot farming, farmer income, availability of infrastructure, and institutional support significantly influenced farmers’ perceptions on the application of technology innovation in shallot cultivation. Adoption trends indicate that some components will be adopted in the next growing season.